MiR-93-5p promotes granulosa cell apoptosis and ferroptosis by the NF-kB signaling pathway in polycystic ovary syndrome - Tan, Wei; Dai, Fangfang; Yang, Dongyong; Deng, Zhimin; Gu, Ran; Zhao, Xiaomiao; Cheng, Yanxiang (Frontiers in Immunology, 2022)
Abstract Purpose: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age. miR-93-5p has been reported to be elevated in granulosa cells of PCOS patients. However, the mechanism by which miR-93-5p drives granulosa cell (GC) progression remains unclear. Thus, this study focuses on the roles and mechanisms of miR-93-5p in the GCs of PCOS. Methods: KGN cells have similar ovarian physiological characteristics and are used to study the function and regulatory mechanism of GCs. In this study, KGN cells were transfected with si-NC, si-miR93-5p, oe-NC and oe-miR93-5p. A cell counting kit-8 assay, flow cytometry and western blotting were performed to observe the proliferation and apoptosis of KGN in different groups. Subsequently, the levels of reactive oxygen species, malondialdehyde, GPX4, SLC7A11 and Nrf2, which are indicators of ferroptosis, were measured by a dihydroethidium fluorescent dye probe, biochemical kit, western blotting, and PCR. Ultimately, bioinformatic analysis and experimental methods were used to examine the interaction between miR-93-5p and the NF-κB signaling pathway. Results: miR-93-5p was upregulated in the GCs of PCOS patients. Overexpression of miR-93-5p promoted apoptosis and ferroptosis in KGN cells, while knockdown of miR-93-5p showed the reverse effect. Biological analysis and subsequent experiments demonstrated that miR-93-5p negatively regulates the NF- κB signaling pathway. Conclusion: miR-93-5p promotes GC the apoptosis and ferroptosis by regulating the NF-κB signaling pathway. Silencing of miR-93-5p protects against GC dysfunction. Our study identified miR-93-5p as a new molecular target for improving the function of GCs in PCOS patients.